Developing competencies in genetics nursing: Education intervention for perinatal and pediatric nurses - Kyoko Murakami (2020)
© 2020 John Wiley & Sons Australia, Ltd Nurses need to be appropriately trained in genetics to provide clinical care based on best practice for patients and families. This exploratory study describes an educational intervention using authentic stimulus material centered on a clinical case study of a family with a baby with Down syndrome. Quantitative and qualitative data were collected from a sample of 15 nurses and 27 students from three universities in Japan before and after completing an entry-level workshop on competency-based genetics nursing. Participants reported increased perceived genetics knowledge and clinical confidence. Despite more than 90% of the participants reporting that they understood the underlying genetics knowledge, their confidence and the ethical aspects of genetics nursing had not been promoted after the seminar. In contrast, the reflections, coded into three categories, showed they recognized families' needs for psychological support, family decision making, and protection and privacy and suggested that nurses had undergone a profound shift in understanding about these issues. Although indicating that a single seminar was insufficient, the study findings will be useful to develop educational materials on genetics for both students and nurses.